Creativity in teaching: what can teachers learn from artists? - Hall, Christine; Thomson, Pat (Taylor & Francis, 2016)
Since the turn of the century, there have been frequent expressions of concern about a perceived lack of creativity in UK schools, in both curriculum content and in teaching. Recently, as the emphasis on mathematics, science and technology has strengthened, serious concerns have also been expressed about the marginalisation of the arts and creativity in schools. In the light of these concerns, this paper reports in-depth, qualitative research into the pedagogies of practising artists experienced in working with young people and highly valued by the schools that employ them. We use the notion of ‘signature pedagogies’ to argue that the artist–teachers adopted a particular stance and set of pedagogic practices that are coherent and distinctively different to those that are currently officially promoted in UK schools, and that this distinctive pedagogy enhanced both creative practice and engagement in the arts in the schools in which the artists worked. In this paper, we identify the signature pedagogies of the artists, theorise their stance and argue that the findings of our study provide a heuristic which can be valuable to all teachers who are interested in expanding their teaching repertoires and fostering students’ creativity.